New Guidelines on Discretionary Powers - McDougall, Barbara (Refuge: Canada's Journal on Refugees, 1990)
On March 20, 1990 Employment and Immigration Minister Barbara McDougall brought forward new guidelines for immigration officers regarding the application of humanitarian and compassionate considerations when reviewing refugee claims. The guidelines, which we reproduce below, were announced in response to the recent Federal Court of Canada judgement rendered by Associate Chief Justice James Jerome in the case of Ken Yung Yhap. In announcing her response, the Minister rejected any suggestion of an amnesty and said that she intends to continue the refugee backlog clearance program.